If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = -12 + -1e Solving 10 = -12 + -1e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add 'e' to each side of the equation. 10 + e = -12 + -1e + e Combine like terms: -1e + e = 0 10 + e = -12 + 0 10 + e = -12 Add '-10' to each side of the equation. 10 + -10 + e = -12 + -10 Combine like terms: 10 + -10 = 0 0 + e = -12 + -10 e = -12 + -10 Combine like terms: -12 + -10 = -22 e = -22 Simplifying e = -22
| (7x+13)+(7x-2)= | | -2(y-3)=y+4s | | 20x=-80 | | -6y^2=-54 | | [-4g+2]=8 | | -4(6r-7)=35 | | (54x+65y)+(-11x+45y)= | | 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 | | [2x-6]-4=26 | | v^2=8v+2 | | 4*x=88 | | 3*x-18=2*x^2-18+x^2+3*x+9 |